Avaliação do remodelamento atrial em ratos com insuficiência cardíaca induzida pela ablação por radiofrequência do ventrículo esquerdo - um novo modelo experimental de fibrilação atrial - Santos, Luis Felipe Neves Dos [UNIFESP] (2019)
Aims: To evaluate atrial remodeling and AF vulnerability in a rat model of CHF induced by left ventricle (LV) radiofrequency (RF) ablation. Methods: Wistar rats had thoracotomy performed and divided into 3 groups: RF-induced CHF (Ab, n=36), CHF animals treated with spironolactone (AbSpi, n=20) and sham controls (Sham, n=29). After 12 weeks, animals underwent echocardiographic and electrophysiological evaluation and were sacrificed for histological (atrial fibrosis) and western blotting (TGF-β1, Collagen I/III, Cav1.2 and Connexin 43) analysis. Results: Mild LV dysfunction and marked atrial enlargement were noted in both ablated groups. AF inducibility (episodes ≥ 2 seconds) increased in the Ab group compared to sham animals (31/36, 86%; vs. 15/29, 52%; p=0.005), but did not differ from the AbSpi group (16/20, 80%; p=NS). Sustained AF (> 30 seconds) was also more frequent in the Ab group compared to shams (56% vs. 28%; p=0.04). Spironolactone reduced atrial fibrosis (p <0.01) as well as TGF- β1 (p <0.01) and Collagen I/III (p <0.001) expression but did not affect calcium (Cav1.2) nor Connexin 43 expression. Conclusion: Rats with RF-induced CHF exhibit pronounced atrial structural remodeling and enhanced AF vulnerability. This model may be useful for studying AF substrate in CHF.